Contemporary Pygmalion Tales: Robot Sapiens Sapiens. - Ferreira, Maria Aline (Interdisciplinary Humanities)
The article discusses the description of creating life in literature, art, and science in terms of humanoid creatures, homunculi, robots, androids, and cyborgs. Topics discussed include the Pygmalion myth, author Jean-Jacques Rousseau's play "Pygmalion", two dystopian novels; Marge Piercy's "He, She and It" and Jeanette Winterson's "The Stone Gods", and the similarities between narrative in both novels.